Concepção de professores acerca dos conflitos interpessoais entre crianças - Carácio, Flávia Cristina Castilho [UNESP] (2014)
The resolution of interpersonal conflicts is an issue that has been discussed, widely, in the present era, it has been comprehended in the constructivist theory, by confronts, disagreement and frustration social interaction situations, where teacher should stimulates the child to think , expose their ideas and search solutions which could be negotiated considering different points of view, developing a work in dialogue, cooperation and mutual respect logic. This research has its main aim investigate the teacher’s conception in conflict’s resolution among children of first cycle of elementary school, as it is a qualitative study, with exploratory nature, grounded in the constructive theory of Jean Piaget, who understands that the conflicts are necessary for child’s moral development. The data collection was done by half structured interviews with 39 teachers of Elementary schools’ first cycle teachers of four of public schools in interior of Sao Paulo state. For the results, it has done the integral transcription of the interviews and data analysis. The result confirmed the initial hypothesis which teacher need to assume their role in conflicts mediation among kids in association with the parents, principal, and school employee, and that there are gaps in teachers’ formation. Therefore, the study conclusions points the necessity to have spaces for reflection of school professionals daily practices, to contributes with the teacher in the change of the restricted to knowledge transmission education now a days conception to a performance which contributes which values of life in society learning, with solidary and cooperative linkage in school.